Verbal arm swing instructions alter arm-leg interlimb coordination but not prefrontal cortex hemodynamics in people with Parkinson's disease - Zampier, Vinicius Cavassano [UNESP]; Mochizuki, Luis; Beretta, Victor Spiandor [UNESP]; de Belli, Vinicius [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP]; Barbieri, Fabio Augusto [UNESP]; Orcioli-Silva, Diego [UNESP] (Elsevier, 2025)
Verbal instructions related to the arm swing amplitude and velocity change step gait behavior in people with Parkinson's disease (PwPD) and neurotypical individuals. However, how verbal instructions related to upper limb act on interlimb coordination and prefrontal cortex activation are not yet known. Therefore, the aim of this study was to investigate the effects of the instructions to increase arm swing amplitude and velocity during walking on prefrontal cortex (PFC) hemodynamics and arm-leg interlimb coordination in PwPD and neurotypical individuals. Fifteen PwPD and 13 neurotypical individuals walked over a 26.8 m pathway under three experimental conditions: usual walking, walking with increased arm swing amplitude, and walking with increased arm swing velocity. Gait step parameters, continuous relative phase and latency between arm and leg movements, and PFC hemodynamics were calculated. ANOVA two-way (groups x conditions) showed that the verbal instructions to increase arm swing amplitude and velocity during walking improved gait step parameters and arm-leg interlimb coordination, without changing PFC hemodynamics. Specifically, verbal instructions increased average continuous relative phase (F2,52 = 45.5; p < 0.001; ηp2 = 0.63) and decreased the average relative phase variability (F2,52 = 86.9; p < 0.001; ηp2 = 0.77) in both groups and decreased PwPD latency (F2,52 = 3.5; p = 0.03; ηp2 = 0.19). Verbal instructions also increased stride length (F2,52 = 27.7; p < 0.001; ηp2 = 0.51) and velocity (F2,52 = 46.6; p < 0.001; ηp2 = 0.64) and decreased double support phase in both groups. These results allow us to speculate that the engagement of the motor areas to follow the instructions and perform the ensuing action could be related to preservation of some automaticity and it is possible that the participants do not need to use their cognitive resources by increasing PFC activity to process and do the action.